INFILTRATION, EFFECTIVE POROSITY, TRANSMISSIBILITY AND CRITICAL YIELD OF WATER WELLS IN THE CARBONATE FISSURED AQUIFERS OF ATTICA – A CONTRIBUTION TO THE REGIONAL AND MANAGERIAL HYDROGEOLOGY - Kounis, G. D.; Kounis, K. G. (Bulletin of the Geological Society of Greece, 2010)
In the hydrogeological practice and the groundwater resources management the accurate knowledge on the infiltration, effective porosity, transmissibility, and on the sustainable yield of water wells is of fundamental value. It is so, because these parameters are the information primarily required in prediction and decisions relevant to the ground water abstractions and the hydrogeological evaluation of specific sites. In this paper, we present these quantities from the carbonate fissured formations of Attica, non metamorphic (limestones, dolomitic limestones, dolomites ) and metamorphic (marbles), which all are of great areal extent and thus of great interest for groundwater exploitation. In addition, they show good geomorphological, structural and lithologic resemblance with analogous formations elsewhere in this country, so that figures calculated can be reliably transferred for use. In our work we used methods of increased reliability, and having known precipitation (P) we estimated — The Infiltration Index (Ic) from the yield of springs of well defined hydrogeological catchments (natural lysimeters) and results found fall in the range of values 0.38P < Ic < 0.42P — The Effective Porosity (pe), obviously secondary because of the nature of the carbonate aquifers ( fissure flow aquifers ). We calculated it from groundwater level hydrograph and values found are in between 1.31%< pe < 6.91% with the most common in between 1.58%< pe < 4.8% — The Transmissibility (T), we calculated from pumping tests, with Jacob method, using semilogarithmic plots of drawdowns (s) versus time (t) from start of pumping. Values found are mostly (70%)in the range 10m3 /h.m < T < 75m3 /h.m — The Critical Yield (Qc) of water wells we calculated from the “characteristic well curve” Q vs. s (with Q and s standing for yield and drawdown respectively). Values are mostly in between 15m3 /h < Qc <75 m3 /h. Cretaceous limestones showed the best of the parameters, followed by the marbles free of schist in- Δελτίο της Ελληνικής Γεωλογικής Εταιρίας, 2010 Bulletin of the Geological Society of Greece, 2010 Πρακτικά 12ου Διεθνούς Συνεδρίου Proceedings of the 12th International Congress Πάτρα, Μάιος 2010 Patras, May, 2010 tercalations and distant from schist boundary . Karstic processes on the fracture network, structures vulnerable to tectonic extension, like anticlines and tension faulting zones are the underlying reasons for better hydrogeologic performance and thus for higher values of the parameters studied. Dolomites outside the previous zones show very low values .